(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
A Rudimentary horn is a rare form of congenital uterine anomaly, resulting from an arrest in the development of one of the Mullerian ducts with inappropriate fusion with the other side. In most of the cases no direct communicating channel exists between the two parts of the uterus. Pregnancy in the rudimentary horn represents a rare form of ectopic gestation and is thought to result from transperitoneal migration of spermatozoa or the fertilized ovum. Most patients with rudimentary horn pregnancy present in second trimester with hemorrhagic shock due to rupture of horn. Diagnosis of the rudimentary horn may be done with magnetic resonance imaging or 3D, 4D ultrasonography but confirmation of diagnosis is usually surgical at laparoscopy or laparotomy. We report a case with provisional diagnosis of a case of primigravida with 40+ weeks pregnancy with transverse lie along with placenta praevia and intrauterine fetal death. But at laparotomy it revealed a ruptured pregnant non-communicating horn of uterus. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 53-55